Horizontal effect of human rights in debt collection practices by debt collectors in Indonesia - Ahmad Zaky Taqiyuddin (PT WIM Solusi Prima, 2026)
Debt collection practices carried out by debt collectors in Indonesia frequently lead to violations of debtors’ privacy rights, human dignity, and sense of security through intimidation, psychological pressure, and misuse of communication access. This study aims to analyze debt collection practices through the perspective of the horizontal effect of human rights, which extends the obligation to respect human rights not only to the state but also to private actors within civil law relations. This research employs a normative juridical method using statutory and conceptual approaches. The findings indicate that debt collection practices exceeding the limits of propriety potentially violate human rights principles, particularly the rights to privacy, dignity, and legal protection of debtors in Indonesia.